Geographical distribution of Emesis Fabricius (Lepidoptera: Riodinidae) in Mexico: Updated checklist and temporal patterns - Trujano-Ortega, Marysol; Callaghan, Curtis J.; Arellano-Covarrubias, Arturo; Luis-Martínez, Armando; Ávalos-Hernández, Omar; Llorente-Bousquets, Jorge (Zootaxa, 2021)
We present a synthesis of the existing information on the genus Emesis Fabricius in Mexico concerning biogeographical patterns and taxonomical aspects. Emesis is the most diverse genus of Emesidini with 57 species and subspecies, with Mexico as the northern limit of this Neotropical genus. We analyzed 5434 specimens of the Lepidoptera Collection of the MZFC, UNAM and compared them with specimens from collections of Mexico, Central and South America. Taxonomic determination and corroboration were made by analysis of wing patterns and genitalia. Geographic distribution and phenology were obtained from the database MARIPOSA. We present an updated list of Emesis of Mexico, with 17 species and subspecies. For each species, we provide information on phenology, geographic, altitudinal, and vegetation distributions. We discuss taxonomic and undersampling concerns for some species, as well as spatial and temporal patterns with special reference to vegetation types and biogeographic provinces in Mexico.